Algorithm for ranking technological options for grain legumes and dry cereals based on impacts on poverty and malnutrition and economic benefits in over 40 countries using TOPSIS and ShinyApps - CGIAR Research Program on Policies, Institutions, and Markets (2021)
Proof of concept published in 2021.